PENGARUH PENGGUNAAN E-LEARNING TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM KELAS X SEKOLAH MENENGAH ATAS NEGERI 1 SIDOHARJO WONOGIRI - Robbani, Azzam Mulhak; Amin, Lailla Hidayatul; Nashir, Muhammad Ja'far (Faculty of Teacher Training and Education, 2024)
This study aims to analyze the effect of e-learning usage on Islamic Religious Education (PAI) learning outcomes of class X students at Senior High School 1 Sidoharjo in the 2024/2025 Academic Year. The research method used is quantitative with a correlational approach. The population of this study was all class X students of Senior High School 1 Sidoharjo totaling 177 students, with a sample of 74 students selected using the stratified random sampling technique. Data were collected through a questionnaire for the variable of e-learning usage (X) and documentation of report card grades for the variable of learning outcomes (Y). Data analysis was carried out using descriptive statistics and the Pearson Product Moment correlation test to test the hypothesis. The results of the study indicate that the use of e-learning in Islamic Religious Education learning is in the moderate category (62%), while student learning outcomes are also in the moderate category (73%). Hypothesis testing with Pearson Product Moment correlation shows a significant positive effect between the use of e-learning on students' Islamic Religious Education learning outcomes with a significance value of 0.000 (p <0.05) and a correlation coefficient of 0.755. This indicates that the higher the level of e-learning use, the better the student learning outcomes. The conclusion of this study is that e-learning plays a role in improving student learning outcomes in Islamic Religious Education subjects. Therefore, it is recommended for teachers to further optimize the use of e-learning with innovative and interactive learning strategies. The implications of this study indicate that the use of technology in learning can improve the effectiveness of the teaching and learning process.